Innate lymphoid cell recovery and occurrence of GvHD after hematopoietic stem cell transplantation. Issue 1 (13th April 2021) - Piperoglou, Christelle; Larid, Guillaume; Vallentin, Blandine; Balligand, Laura; Crinier, Adeline; Banzet, Nathalie; Farnarier, Catherine; Gomez‐Massa, Elena; Adalia, Aranzazu Cruz; ,; Michel, Gérard; Galambrun, Claire; et al.
Abstract: Lymphocytes are essential for microbial immunity, tumor surveillance, and tissue homeostasis. However, the in vivo development and function of helper‐like innate lymphoid cells (ILCs) in humans remain much less well understood than those of T, B, and NK cells. We monitored hematopoietic stem cell transplantation (HSCT) to determine the kinetics of ILC development in both children and adults. It was found that, unlike NK cells, helper‐like ILCs recovered slowly, mirroring the pattern observed for T cells, with normalization achieved at 1 year. The type of graft and the proportion of CD34 + cells in the graft did not significantly affect ILC reconstitution. As HSCT is often complicated by acute or chronic graft‐versus‐host disease (GVHD), the potential role of ILC subsets in maintaining tissue integrity in these conditions was also analyzed. It was found that GVHD was associated with lower levels of activated and gut‐homing NKp44 + ILCP, consistent with a non‐redundant role of this ILC subset in preventing this life‐threatening disorder in lymphopenic conditions. Graphical Abstract: Patients with graft‐versus‐host disease after hematopoietic stem cell transplantation showed slow recovery of circulating innate lymphoid cells and a reduced number of activated ILCP; this is consistent with a non‐redundant role of this ILC subset in preventing this life‐threatening disorder under lymphopenic conditions.